Critical Review: De la Hipótesis a la Tesis en Traducción e Interpretación, by Antonio Bueno, Jana Králová and Pedro Mogorrón - López Ruiz, María del Carmen (2021)
This book review addresses the collective book entitled De la hipótesis a la tesis en Traducción e Interpretación, edited by Antonio Bueno, Jana Králová and Pedro Mogorrón. This work is the output of the Virtual Conference “De la hipótesis a la tesis en Traducción e Interpretación” [From Hypothesis to Thesis in Translation and Interpreting Studies], which was held online by the University of Valladolid (Spain) in February 2019. The book describes the current state-of-the-art concerning Translation and Interpreting Studies within several doctoral programmes of international universities. The 32 chapters composing the book are gathered together around eight different specialised topics.